Answers

2014-07-07T01:21:08+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Multiply equation 1by a and equ 2 by b we get a^2x +aby -2a^2 + 3ab =0 ...........(3). b^2x -aby -3ab -2b^2 =0 .........,,,.(4). Now adding equ 3and 4 we get x(a^2+b^2) -2(a^2+b^2) =0 => x = -2 answer
1 5 1
Put x= 2 in equ 1 we get 2a + by -2a +3b=0 => by = -3b => y= -3 answer
Thanks a lot
Can you please answer my other questions
You can find them in my profile
Mark as best plz